Ask your own question, for FREE!
Mathematics 57 Online
OpenStudy (anonymous):

Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. -3x + 4y = 1 -6x + 6y = -3 Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. -3x + 4y = 1 -6x + 6y = -3 @Mathematics

OpenStudy (katrinakaif):

-2(-3x + 4y) = 1(-2) ---> +6x - 8y = - 2 - 6x + 6y = -3 -2y = -5 y = 5/2 Now plug it back into find x! =))

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!